Jerusalem, Alexandria, Rome: studies in ancient cultural interaction in honour of A. Hilhorst - Luttikhuizen, Gerard P.; García Martínez, Florentino (Journal for the study of Judaism, 2003)
The present volume has been compiled by colleagues and friends as a tribute to Dr. A. Hilhorst, the Secretary of the Journal for the Study of Judaism, on the occasion of his 65th birthday. Its 23 contributions by renowned international experts, reflect the various interests of the honouree, his approach to the Classical and Semitic languages and literatures as forming part of a continuum, and his attention to the interactions between the different literary corpora.Several contributions deal with the interaction of the Old Testament with later Jewish, Gnostic, or Christian writings; others explore the influences of Greek writings within a Jewish context at the levels of philology, of theological ideas, of realia, or of influence of literary compositions. Furthermore, a number of contributions centers on the interaction of Greek motives in Jewish and Christian literature, whereas in several others the focus is on the Martyrium literature or on early Christian texts